(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Harahap IS, Asnan TAW, Widayanti S, Widhiastuti H. 2022. Diversity and composition of ant species in different urban areas in Bogor, West Java, Indonesia. Biodiversitas 23: 4090-4096. Land use change, from natural to urban areas, is a threat to biodiversity because the disturbance created by human can destroy the habitat and decrease species richness. Ant is one of the most abundant animals in tropical habitats and most intrusive in an urban area. This research aims to determine the types of ants commonly found in various urban ecosystems in Bogor, West Java, Indonesia. Ant observation and sampling were carried out in Bogor City Areas at four different urban ecosystems, i.e., office area, shopping mall, housing area, and bus station. At each sampling location, ten observation plots were taken under different environmental conditions. Sampling was carried out for 6 months, from April to October 2021 with the direct collection and trapping method. The sample was then carried out to the laboratory for identification and data analysis process. The results of the species inventory obtained 7532 individuals and 28 species from 4 subfamilies, namely Dolichoderinae, Formicinae, Myrmicinae, and Ponerinae. The diversity of ant species at each location showed that the ant species in the bus station were not significantly different from the mall area. However, the diversity of ant species in three locations, namely bus stations, malls, and housing estates, showed significant differences with the diversity of ant species in office habitats. Anoplolepis gracilipes which is an invasive tramp species, is one type of ant found in all sampling locations with a relatively high abundance.